ANALYSIS OF THE EFFECT OF VSM ON THE MEMORY ACQUISITION PROCESS USING THE DYNAMIC ANALYSIS METHOD - Sinta Nur Maulina; Niken Dwi Wahyu Cahyani; Erwid Musthofa Jadied (STKIP PGRI Tulungagung, 2023)
At first, forensics was restricted to studying data that was stored on a system's hard disk. However, as storage capacity and data encryption increased, applying conventional digital forensic procedures became more challenging. As a result, memory forensics techniques are developed, or are frequently referred to as live forensics, because the process is quicker and more sophisticated. Volatile memory forensics, often known as live forensics, are necessary for this condition. Live forensics has flaws, specifically that some programs can fail when the computer is in active VSM (virtual secure mode). This results in the retrievable evidence being lost. Therefore, determining the cause is essential. The software-based memory acquisition tools Autopsy, Isobuster, DumpIt, and Magnet RAM Capturer are just a few examples. According to the findings of the experiments, the tools that have crashed include DumpIt v1.3.2.20110401. A dynamic code analysis using WindBg as a tool was utilized to study the impact of VSM on the memory acquisition tool. This study's goal is to identify the instances of crashes in various forensic instruments, which will be highly useful for forensic experts performing investigations.